BREAKING THE MIRROR: 'I LOVE ME' MOVEMENT AND THE REBELLION AGAINST BEAUTY IDEALS ON MEDIA X - Khairiah, Nona; Sazali, Hasan (International Journal of Cultural and Social Science, 2025)
This article aims to examine how the "I Love Me" movement utilizes social media to challenge conventional beauty standards and promote values of diversity and self-acceptance. The urgency of this research arises from significant issues faced by modern society, where social media often promotes beauty standards that are not only unrealistic but also exclusive and detrimental. These standards can potentially cause body image disorders and social anxiety, especially among teenagers and adults, making this research not only academically relevant but also crucial for public health and social policy. This research employs a qualitative approach with netnographic methods within a constructivist paradigm to understand the dynamics of communication and self-representation on social media related to the "I Love Me" movement. The study was conducted by collecting primary data through the social media analysis application Keyhole, which provides frequency, reach, and types of interactions related to the campaign or hashtag used by the movement. Secondary data were also gathered from various sources including books, scholarly articles, and media reports discussing beauty standards, the influence of social media, and related social movements. Data collection techniques include systematic media observation and documentation, and data analysis was performed using the methods of Miles, Huberman, and Saldana, which involve data conditioning, categorization, and systematic conclusion drawing. The findings indicate that the "I Love Me" movement has successfully created a dialogue that supports physical diversity and promotes mental health by challenging the dominant commercial and harmful beauty narratives. The movement demonstrates its effectiveness in leveraging social media to change beauty perceptions, reduce stress and pressure related to body image, and support self-acceptance and beauty in all forms.